Chris Gardner’s Struggle Reflected on The Pursuit of Happyness Movie: An Individual Psychological Approach - Alya Rahma Adriani; Abdillah Nugroho (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Every person's life is riddled with difficulties. There is a movie that portrays how struggle life is, entitled The Pursuit of Happyness. The writer uses a psychological technique to assess Chris Gardner's struggle for a better life in this research. The research was conducted using a descriptive qualitative method. The result shows that the movie focuses on Chris, who had a hard time making ends meet. This movie conveys the message of self-reliance, optimism, and self-confidence.